Visuospatial imagery in healthy individuals with different hypnotizability levels. (18th January 2019) - Incognito, Oriana; Menardo, Elisa; Di Gruttola, Francesco; Tomaiuolo, Francesco; Sebastiani, Laura; Santarcangelo, Enrica L.
Highlights: Mental rotation (MR) implies efficient cerebellar function. Hypnotizability-related cerebellar morpho-functional differences have been found. MR accuracy is greater in subjects with high/low than medium hypontizability scores. Different mechanisms of mental rotation could operate in highs, mediums and lows. Abstract: Hypnotizability is a psychophysiological trait associated with morpho-functional brain differences. Since also cerebellar peculiarities have been reported in individuals with different hypnotizability levels and the cerebellar function is relevant to spatial imagery, the present study was aimed at investigating possible hypnotizability-related differences in the ability of spatial imagery. Highly (highs, N = 31), low (lows, N = 17) and medium (mediums, N = 16) hypnotizable participants (classified by Stanford Hypnotic Susceptibility Scale, form A) of both genders were submitted to a test of mental rotation, which requires the integrity of both executive and cerebellar structures. In order to disentangle the role of the cerebellum from that of executive circuits as much as possible, visuospatial and verbal working memory tests, which mainly reflect executive processes, were also performed. Healthy highs exhibited higher scores of mental rotation ability compared to mediums in the absence of significant differences in visual-spatial and verbal working memory. Lows reported intermediate scores not significantly different from both highs' and mediums'. Different cognitive strategies were observed in the three groups as the correlations between mental rotation, visuospatial and verbal working memory were different in highs, mediums and lows. In conclusion, present findings represent the first report of hypnotizability-related differences in a mental rotation task, which is relevant to several cognitive functions.